Sleep and breathing in children with Joubert syndrome and a review of other rare congenital hindbrain malformations - Jia-Der Ju-Wang; Jennifer C. Dempsey; Cristian Zhang; Daniel Doherty; Manisha Witmans; Mary Anne Tablizo; Maida Lynn Chen (Therapeutic Advances in Respiratory Disease)
Background: Joubert syndrome (JS) is an autosomal recessive disorder with a distinctive mid-hindbrain malformation known as the “molar tooth sign” which involves the breathing control center and its connections with other structures. Literature has reported significant respiratory abnormalities which included hyperpnea interspersed with apneic episodes during wakefulness. Larger-scale studies looking at polysomnographic findings or subjective reports of sleep problems in this population have not yet been published. Objectives: The primary objectives were (1) compare a large group of children with JS and their unaffected siblings for caregiver-reported sleep difficulties. Secondary objectives were (1) present new polysomnography (PSG) data on our JS cohort; (2) review sleep disordered breathing (SDB) in other rare congenital hindbrain anatomic abnormalities. Design: We conducted a cross-sectional study on a cohort of 109 families affected by JS. Methods: Pediatric Sleep Questionnaire (PSQ) and the Children’s Sleep Habits Questionnaire (CSHQ) along with general medical health information focused on respiratory and sleep problems were mailed to all patients and families. Caregivers were asked to complete the survey for both children with JS and unaffected siblings, if any. Baseline diagnostic PSG was retrospectively reviewed for those with available studies, and the sleep parameters were compared to a referent cohort. Results: Study participants with JS were older than their unaffected siblings ( p  = 0.02). Genetic mutations were available for 41 out of 118 individuals, with the most common mutation being MKS3 (31.4%). Patients with JS had higher scores in the PSQ compared to their unaffected siblings ( p  < 0.001). PSG data showed severe SDB with apnea-hypopnea index (AHI) of 23 ± 15 events/h in patients with JS. Events were primarily obstructive (obstructive AHI 18 ± 15 events/h vs central AHI 4 ± 4 events/h). Abnormal sleep architecture with increased arousal indices, decreased efficiency, and more time awake and in light sleep or wakefulness when compared to the referent data. Conclusion: SDB is common and severe in patients with JS, and the significantly greater obstructive component reported in this cohort makes it necessary to perform complete PSG studies to address or prevent clinical manifestations in this at-risk population. PSQ could represent a viable method to screen for SDB in JS.